Interaksi Masyarakat Melalui Tradisi Dan Ritual Sosial - Nabilla Alya Nanda; Destya Suci Alvionita; M. Amirul Faros (Bahasa Indonesia, 2025)
This study aims to analyze Muslim community interactions with the Qur’an through traditions and social rituals as an actualization of the Living Qur’an concept. Previous Qur’anic studies have predominantly focused on textual interpretation, while the socio-cultural dimension that frames the Qur’an in daily life has received less scholarly attention. To address this gap, this research employs a qualitative method with a library research approach, collecting data from primary and secondary literature related to religious practices and Muslim community traditions. The findings reveal that the Living Qur’an is not limited to reading and memorization but also manifests in social practices such as tadarus, khataman, tahfidz, as well as religious and cultural rituals like marriage, circumcision, and tahlilan. These practices function as means of internalizing moral, ethical, and spiritual values that strengthen social solidarity, construct collective identity, and sustain local culture. The study emphasizes that the Living Qur’an represents an integration of sacred text and dynamic social reality. In conclusion, the Living Qur’an offers a significant paradigm for understanding the Qur’an’s role as a moral guide, a medium of cultural transformation, and a foundation for shaping Muslim community character amid modernization and globalization.